Compact design of circularly polarized microstrip patch antenna with double slip ring resonator for vehicle-to-vehicle communication - Zaw, Ko Ko; Khin, Ei Ei; Oo, Thandar; Pradhan, Devasis; Tun, Hla Myo (Journal of Engineering Researcher and Lecturer, 2024)
The paper mainly focuses on the compact design of circularly polarized microstrip patch antenna for vehicle-to-vehicle communication. The charging time of electric vehicle is longer waiting time than compared to traditional gasoline-based vehicles. The charging is done at the public charging stations. When the vehicles need charging while driving, they communicate with Dedicated Short Range Communications (DSRC) band to send the information to the nearest vehicles and receive information from the charging station. Moreover, DSRC band is used in many applications area such as Intelligent Transportation System (ITS), Electronic Toll Collection (ETC), Collision Avoidance, and connected vehicles. The research problem in this study is that when installing an antenna on a vehicle, it is important to have a compact size and achieve circular polarization. The research solution for the problem statement in this study is emphasized on 45? inclined slot and corner trimmed is added in rectangular patch to make the current part longer and the impedance matching better, and to get circular polarization. After that, Swiss roll structure CSRR is added in ground plane to improve bandwidth. Finally, outer SRR is added in the ground plane to improve S11. The proposed design has been validated for car-to-car (5.85-5.925 GHZ) communication.